2021
DOI: 10.1126/sciimmunol.abf9792
|View full text |Cite
|
Sign up to set email alerts
|

KIR3DL3-HHLA2 is a human immunosuppressive pathway and a therapeutic target

Abstract: The B7 family ligand HERV-H LTR–associating protein 2 (HHLA2) is an attractive target for cancer immunotherapy because of its coinhibitory function, overexpression in human cancers, and association with poor prognoses. However, the knowledge of the HHLA2 pathway is incomplete. HHLA2 has an established positive receptor transmembrane and immunoglobulin (Ig) domain containing 2 (TMIGD2) but a poorly characterized negative receptor human killer cell Ig-like receptor, three Ig domains, and long cytoplasmic tail (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 57 publications
4
86
1
Order By: Relevance
“…15 , 25–27 Therefore, immune-related processes should attract special attention, which might be a potential mechanism that mediates the tumor promoter role of HHLA2 in PTC. 10 , 26 Further mechanism investigations that would leak out the signaling and receptors of HHLA2 are warranted, which would be a part of the future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 , 25–27 Therefore, immune-related processes should attract special attention, which might be a potential mechanism that mediates the tumor promoter role of HHLA2 in PTC. 10 , 26 Further mechanism investigations that would leak out the signaling and receptors of HHLA2 are warranted, which would be a part of the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, the role of HHLA2 in immune regulation also implies the potential of HHLA2 in immunotherapeutic approaches as well as in the therapy of PTC. 15,[25][26][27] Therefore, immune-related processes should attract special attention, which might be a potential mechanism that mediates the tumor promoter role of HHLA2 in PTC. 10,26 Further mechanism investigations that would leak out the signaling and receptors of HHLA2 are warranted, which would be a part of the future studies.…”
mentioning
confidence: 99%
“…separately and simultaneously identified that KIR3DL3 was an inhibitory receptor of HHLA2 and KIR3DL3-HHLA2 axis was an immunosuppressive pathway in cancer immunity, making HHLA2-related studies step into a new chapter. 7 , 8 …”
Section: Role Of Hhla2 In Cancer Developmentmentioning
confidence: 99%
“…Recently, studies on a promising immune checkpoint, Human endogenous retrovirus-H long terminal repeat-associating 2 (HHLA2), are flourishing because its co-inhibitory receptor, killer cell Ig-like receptor, three Ig domains, and long cytoplasmic tail (KIR3DL3), is newly identified. 7 , 8 This makes HHLA2-KIR3DL3 pathway a novel potential target for cancer immunotherapy. HHLA2, also known as B7-H7/B7y, is a type Ι transmembrane protein that belongs to B7 family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation